2020
DOI: 10.3390/medicina57010028
|View full text |Cite
|
Sign up to set email alerts
|

Lipid and Glycemic Profiles in Patients with Bipolar Disorder: Cholesterol Levels Are Reduced in Mania

Abstract: Background and Objectives: Bipolar disorder (BD) is a severe mental condition with a lifetime prevalence estimated around 2% among the general population. Due to risk factors, etiological mechanisms, and the chronic use of psychotropic medications, people with BD are frequently affected by medical comorbidities, such as metabolic syndrome (MetS), associated with altered blood levels of glucose, cholesterol, and triglycerides. Moreover, the lipid concentration may be associated with the severity of psychiatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…In the SCZ, BD-M, and BD-D groups, the BD-D group showed the highest CHO, LDL, and Apo B, followed by the SCZ group; the BD-M group showed the lowest CHO, LDL, and Apo B; furthermore, the SCZ group showed the lowest HDL. Several reports had identified lower cholesterol levels in BD manic patients than in the euthymic phase or BD depressive patients ( 51 ), which was in line with our results. Cholesterol is a principal component of the cell membrane and plays an important role in synaptic functions, and the depletion of cholesterol may induce the alteration of brain signaling, with effects on several neurotransmission systems ( 48 , 52 ).…”
Section: Discussionsupporting
confidence: 93%
“…In the SCZ, BD-M, and BD-D groups, the BD-D group showed the highest CHO, LDL, and Apo B, followed by the SCZ group; the BD-M group showed the lowest CHO, LDL, and Apo B; furthermore, the SCZ group showed the lowest HDL. Several reports had identified lower cholesterol levels in BD manic patients than in the euthymic phase or BD depressive patients ( 51 ), which was in line with our results. Cholesterol is a principal component of the cell membrane and plays an important role in synaptic functions, and the depletion of cholesterol may induce the alteration of brain signaling, with effects on several neurotransmission systems ( 48 , 52 ).…”
Section: Discussionsupporting
confidence: 93%
“…BD represents a leading cause of burden worldwide and contributes significantly to premature death [2]. Subjects with BD are at high risk of presenting with co-occurrent psychiatric illnesses, including alcohol and substance use disorders [3][4][5], as well as serious medical comorbidities [3,[6][7][8][9][10]. Moreover, suicide risk is up to 30 times higher in individuals with BD than the general population, with one in four to five subjects attempting suicide lifetime [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that BPD patients experiencing a manic episode had significantly lower total cholesterol, high-density lipoprotein (HDL), and LDL than euthymic patients. The BPD patients have significantly lower total cholesterol and LDL levels in (hypo)manic than depressed patients ( Fusar-Poli et al, 2020 ), indicating a greater oxidative stress in manic episode. As such, the decreased oxidation of LDL was related to the alleviation of manic symptoms in BPD.…”
Section: Discussionmentioning
confidence: 98%